Socialization of Groundwater Treatment with Modified IPA Prototype in Doyomulyo, Lamongan District - Eko Sulistiono; M. Hanif; Gading Wilda A; Marsha Savira A; Rizky Rahadian W; Nur Lathifah S; Denaya Andrya P; Amanda Aulia MP (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Doyomulyo is a village located in Lamongan residents , most of the population's livelihood as a farmer. The village is also known have a source of groundwater. Even during a drought these sources remain abundant. Doyomulyo Village is indeed included in the drought-prone map during the rainy season like now. However, Donomulyo Village still has a source of raw water that is used for daily needs. One of them is near the Donomulyo Village hall mosque, but the water source is adjacent to the mosque's bathroom septic tank. So the laboratory results show the results of DO, TDS, COD, BOD, Total Coliform and E. Coli which do not meet the standards. And there is the desire of the people of Doyomulyo Village, Kembangbahu District, Lamongan Regency to produce groundwater into bottled drinking water (AMDK). So that Unisla through community service activities wants to improve the quality of Doyomulya village water sources so that they become drinking water that is ready for consumption. In Community Service (PKM) activities, the team used a groundwater treatment method with a modified IPAM prototype. Based on the results of groundwater characteristics obtained, the design of equipment for the drinking water treatment unit in Doyomulyo, Lamongan Regency requires that the filter media for the filter tube are activated carbon, silica sand and manganese zeolite used to remove dissolved particles above 50 µ in size and can also reduce concentration of iron and organic matter contained. Community Service Program (PKM) activities by FIKES UNISLA in Doyomulya Village have resulted in a planning program for drinking water treatment to increase the demand for drinking water for residents of Doyomulya Village and its surroundings.